An Analysis of Electric Car Advertisement Language on YouTube Platform - Sayd, Anastasia Imelda; Nazarudin, Hamzah; Seubelan, Alfiando (FKIP - Universitas Tanjungpura, 2025)
This study investigates the language styles, functions, strategies, and imaging strategies of English-language electric car advertisements that appear on YouTube. The study adopted a qualitative descriptive method, employing data collection techniques such as recording, observation, and note-taking. Data analysis was conducted using Miles and Huberman's interactive model, integrated with Braun and Clarke